1994
DOI: 10.1021/bi00167a016
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition and inactivation of the F1 adenosine triphosphatase from Bacillus PS3 by dequalinium and activation of the enzyme by lauryl dimethylamine oxide

Abstract: The F1-ATPase from Bacillus PS3 (TF1) hydrolyzes 50 microM ATP in three kinetic phases. An initial burst rapidly decelerates to a partially inhibited, intermediate phase, which, in turn, gradually accelerates to an uninhibited, final steady-state rate. Lauryl dimethylamine oxide (LDAO) stimulates the final rate over 4-fold. The stimulatory effect saturates at about 0.1% LDAO. Under these conditions, the intermediate phase is nearly absent. Dequalinium inhibits TF1 reversibly in the dark in the presence or abse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 33 publications
3
45
1
Order By: Relevance
“…A lag phase was also reported when TF 1 hydrolyzed 2 M ATP (60). However, it was reported that hydrolysis of 50 M ATP by TF 1 started with a burst but not a lag (61). Hydrolysis of TNP-ATP was reported to be chase-promoted by ATP (41), but no chase-promotion was observed in the experiment in this report (Fig.…”
Section: Fig 6 Re-isolation and Analysis Of Activated Subunit Complexmentioning
confidence: 44%
“…A lag phase was also reported when TF 1 hydrolyzed 2 M ATP (60). However, it was reported that hydrolysis of 50 M ATP by TF 1 started with a burst but not a lag (61). Hydrolysis of TNP-ATP was reported to be chase-promoted by ATP (41), but no chase-promotion was observed in the experiment in this report (Fig.…”
Section: Fig 6 Re-isolation and Analysis Of Activated Subunit Complexmentioning
confidence: 44%
“…2A compare hydrolysis of 2 mM ATP by the wild-type complex before and after incubation with ADP plus Mg 2ϩ . As observed for intact TF 1 (23,45), trace a illustrates that the wild-type ␣ 3 ␤ 3 ␥ complex hydrolyzes 2 mM ATP with a pronounced lag. The final rate of ATP hydrolysis in trace a is 18 mol/mg/min.…”
Section: Methodsmentioning
confidence: 67%
“…Three kinetic phases are observed when MF 1 , TF 1 , and the ␣ 3 ␤ 3 ␥ subcomplex of TF 1 hydrolyze low concentrations of ATP (8,22,23). An initial burst rapidly decelerates to a slow, intermediate rate, which, in turn, progressively accelerates to the final steady-state rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…S1 and S2). Lauryldodecylamine oxide has been thought to help F 1 not to lapse into ADP-Mg inhibition (23). The FRET change became faster in the presence of lauryldodecylamine oxide, while the time course of recovery of ATPase was almost unchanged 5 .…”
Section: Discussionmentioning
confidence: 99%